Studying the Relationship Between Developmental Math Student Attitudes and Academic Achievement - Olson, Jasmine (My University, 2014)
The purpose of this study was to examine the relationship between students' levels of confidence and anxiety and academic achievement in a math course.
Color poster with text, tables, and graphs.
Keywords: Mathematics learning; Attitudes--College students; Academic achievement; Posters